Economic Situation and Development Perspectives of Farms in Poland - An Analysis Based on Survey Data from Selected Polish Voivodships and a Comparison with German Farms - Martin Petrick; Grzegorz Spychalski; Michal Switlyk; Ewa Tyran (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
The aim of this paper is to present an analysis of farm-level data collected in a survey of 464 Polish farms in 2000. Performance indicators of farms in three Polish voivodships are compared with farm accountancy data from two German Lan̈der. The results show that Polish farms are much less profitable than their German counterparts. The gap in income levels is much higher between persons employed in the agricultural sector than between average working persons in the two countries. Living standards of the Polish farm population in the north-west exceed those in the south-east of the country. The analysis suggests that the lower profitability of farms has two major reasons. First, farms in the German regions receive much higher levels of subsidies. Second, there are pronounced structural deficiencies due to a quite unfavourable workforce-land ratio on Polish farms. These farms are less productive and less specialised than the German farms analysed. There is a generally conservative attitude among Polish farmers that prefers the continuation of farming over leaving the sector. Nevertheless, income from agriculture is to a substantial extent complemented by off-farm employment in the southern regions. Our overall conclusion is that Polish farms currently are in the midst of a regional, economic, and social differentiation process fuelled by severe imbalances in terms of income levels between rural and urban population groups. This process is however seriously slowed down or even halted by a number of effective institutional barriers, particularly with regard to rural labour markets. These barriers should be properly addressed by a formulation of future policies in order to avoid further social frictions in the course of the Polish EU accession.
Keywords: 330; Landwirtschaft; Betriebsvergleich; Rentabilität; Wirtschaftlichkeit; Internationaler Wettbewerb; Polen; Deutschland